Wpływ inhibitora syntazy tlenku azotu (L-NAME) na ciśnienie śródgałkowe u szczurów w przebiegu zapalenia błony naczyniowej indukowanego endotoksyną - Szymaniec, Stanisław; Misiuk-Hojło, Marta (Klinika Oczna / Acta Ophthalmologica Polonica, 2002)
We studied the influence of the nitric synthase inhibitor (L-NAME) on the induction of uveitis in Wistar rats. The inflammation was induced by a footpad injection of endotoxin in rat. The clinical signs were evaluated in a slit-lamp, the intraocular pressure was measured using Tono Pen tonometer. We showed, that in endotoxin-induced uveitis the intraocular pressure elevation was observed and that L-NAME application reduced the inflammation and the level of the intraocular pressure.